Equitable Exchange: A Framework for Diversity and Inclusion in the Geosciences. Issue 2 (12th May 2021) - Harris, L. A.; Garza, C.; Hatch, M.; Parrish, J.; Posselt, J.; Alvarez Rosario, J. P.; Davidson, E.; Eckert, G.; Wilson Grimes, K.; Garcia, J. E.; Haacker, R.; Horner‐Devine, M. C.; et al.
Abstract: We highlight a mechanism for the coproduction of research with local communities as a means of elevating the social relevance of the geosciences, increasing the potential for broader and more diverse participation. We outline the concept of an "Equitable Exchange" as an ethical framework guiding these interactions. This principled research model emphasizes that "currencies"—the rewards and value from participating in research—may differ between local communities and geoscientists. For those engaged in this work, an Equitable Exchange emboldens boundary spanning geoscientists to bring their whole selves to the work, providing a means for inclusive climates and rewarding cultural competency. Plain Language Summary: This study expands on prior work to outline an ethical framework to guide research cocreated with local communities. We propose appreciation for the differing perspectives geoscientists and local community members bring to problem‐solving and to creating knowledge around questions and issues pertinent to geoscience. A respectful and "Equitable Exchange" between individuals working together in these contexts can foster greater scientific creativity and societal relevance, and may ultimately broaden and diversify participation in the geosciences. Key Points: We need new mechanisms to broaden participation in the geosciences Co‐production of science with local underrepresented communities may improve societal relevance and diversify geosciences The Equitable Exchange creates an ethical framework for coproduction and inculcates skills related to cultural competency and attention to inclusive practices into the geosciences